Compositional Similarity of Urban Green Areas in Southeastern Brazil - Ronaldo Oliveira dos Santos; Rubiene Neto Soares; Breno Marques da Silva e Silva (Floresta e Ambiente, 2019)
ABSTRACT Urban afforestation greatly contributes to the ex situ conservation of native species in urban centers of Brazil. In this way, the aim of the present work was to analyze the similarity of the arboreal-shrub flora among urban afforestation in southeastern Brazil. For this analysis, a binary matrix with data of 283 species present in 20 municipalities in the Southeastern Region of Brazil was adopted, in which the Principal Component Analysis (PCA) was also used aiming at enabling refinement in the grouping obtained by the floristic similarity (FS) of Sørensen with similarity from values provided by PCA. FS among municipalities was intermediate, but the highest similarity of urban flora was found among the geographically closest municipalities. In the southeastern region, 283 species were recorded, being distributed in 71 botanical families, with Fabaceae having the largest number of species, and with emphasis on the predominance of exotic plants over native plants.